Teachers’ Perceptions of their Learners, Teaching and Rurality in Mathematics Teaching - Mbhiza, Hlamulo Wiseman; Zondo, Ayanda Sizwe (Indonesian Journal of Education and Social Sciences, 2025)
This qualitative multiple case study investigates the interplay between teachers' perceptions, their pedagogical approaches, and the unique challenges of teaching mathematics in rural South African schools. Drawing on semi-structured interviews and Video-Stimulated Recall Interviews (VSRIs) with 5 Grade 10 teachers in Acornhoek, Mpumalanga Province in South Africa, the research reveals how teachers' beliefs about their learners' capabilities and the socio-economic context shape their teaching practices. The findings indicate that teachers often resort to ritualized discourse and direct instruction, limiting opportunities for learners to engage in critical thinking and problem-solving. This reliance on teacher-centred approaches is attributed to perceived deficiencies in learners' foundational knowledge and a lack of resources, which teachers believe necessitate a more directive teaching style. Furthermore, the study highlights the cultural sensitivities that influence pedagogical choices, as teachers navigate local norms that restrict the use of relatable examples in mathematics teaching. The reluctance to incorporate culturally responsive teaching practices underscores the need for teachers to connect mathematical concepts to learners’ lived experiences. Through employing Fairclough's Critical Discourse Analysis, the research uncovers the underlying perceptions that inform teachers' strategies and their implications for learner engagement and understanding. Ultimately, the study calls for a re-evaluation of teaching practices in rural mathematics education, advocating for approaches that foster active participation and enhance the educational experiences of rural learners. This study contributes to the field by illuminating how rural South African mathematics teachers’ perceptions and socio-cultural contexts shape their pedagogical choices, revealing a reliance on directive teaching practices that limit learner engagement and highlighting the need for culturally responsive, learner-centred approaches to improve mathematics education in under-resourced settings.